2013
DOI: 10.1177/0146167213490806
|View full text |Cite
|
Sign up to set email alerts
|

The Social Value of Being Ambivalent

Abstract: We tested whether individuals can exert control over the expression of attitudinal ambivalence and if this control is exerted with self-presentational concerns. Using the self-presentation paradigm, participants reported more ambivalence about Genetically Modified Organisms (GMOs) in a standard and a self-enhancement (present yourself positively) conditions than in a self-depreciation (present yourself negatively) condition, on felt (Experiments 1a and 2a) and potential ambivalence, in its cognitive (Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Studies using these paradigms have demonstrated the positive social value of internality (Dubois, 2008), individualism (Dubois & Beauvois, 2005), belief in a just world (Alves & Correia, 2008, and ambivalence (Pillaud, Cavazza, & Butera, 2013). What these norms have in common is the fact that they contain ideas that are fundamental for the structures of our modern occidental societies (Beauvois, 2003).…”
Section: The Sociocognitive Approach To Social Normsmentioning
confidence: 99%
“…Studies using these paradigms have demonstrated the positive social value of internality (Dubois, 2008), individualism (Dubois & Beauvois, 2005), belief in a just world (Alves & Correia, 2008, and ambivalence (Pillaud, Cavazza, & Butera, 2013). What these norms have in common is the fact that they contain ideas that are fundamental for the structures of our modern occidental societies (Beauvois, 2003).…”
Section: The Sociocognitive Approach To Social Normsmentioning
confidence: 99%
“…In the case of ambivalence, previous work shows that people regulate the expression of ambivalent attitudes based on the impression they aim to create on others. Specifically, people reported more ambivalence when they aimed to generate a positive impression, which they seemed to do by default in a baseline condition, in comparison with when they intended to generate a negative impression ( Pillaud et al, 2013 ). The authors argue that the expression of ambivalence can function as a cue of social competence when discussing controversial topics, i.e., when others may appreciate pondered and balanced information about both sides of a controversy ( Pillaud et al, 2013 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although our interpretation of the link between ambivalence and interpersonal liking has mainly focused on its affective nature, this does not exclude the possibility that people strategically express ambivalence for other reasons. Ambivalent individuals might indeed be positively perceived based on their image of competence for offering pondered and balanced perspectives about controversial topics (Pillaud et al, 2013(Pillaud et al, , 2018. Furthermore, a growing line of research highlights the benefits of ambivalence for cognitive and emotional regulation, such as increase of attention and creativity (Fong, 2006), less biased decision-making (Guarana and Hernandez, 2016), higher estimation accuracy (Rees et al, 2013), and more effective coping with outcome uncertainty (Plambeck and Weber, 2009;Reich and Wheeler, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Study 2 examined whether people's intention when expressing ambivalence is indeed the social validation of the attitudinal conflict experienced by ambivalent others. While it has been suggested that ambivalence functions as a cue of social competence when addressing a controversial topic (Pillaud et al, 2013(Pillaud et al, , 2018, the expression of ambivalence may also be intended as a validating framework for those ambivalent others who experience an attitudinal conflict. The aim of Study 2 was to address this issue directly and, at the same time, offer a conceptual replication of Study 1.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation